Do sentimental investors price rational information? Evidence from the Boston Celtics. Issue 9 (19th May 2020) - Carter, Kelly
Abstract : Purpose: Much evidence exists that rational investors factor rational information into their valuation of shares. This paper aims to examine whether sentimental investors do the same. Design/methodology/approach: To investigate this issue, the author measures sentimental investors' reaction to the surprise player transactions of the Boston Celtics, which traded on the New York Stock Exchange for 18 years. The team's shares were bought mainly as souvenirs by sports fans, whose largely unwavering support makes them perhaps the least likely investors to be influenced by rational information. Thus, if the team's share price changes because of the arrival of rational information, evidence that sentimental traders price rational information into their valuation of a stock will exist. Findings: An acquired player's salary, education and firm-specific experience with the Boston Celtics cause higher returns. This result provides evidence that sentimental traders factor rational information into their valuations of shares. On a broader scale, the findings underscore the importance of rational information to the valuation process, as even sentimental investors price rational information into a stock that is held for sentimental reasons. Moreover, the results are consistent with the nudge theory, in that the arrival of rational information encourages (i.e. nudges) sentimental investors to price the rational information as a rational investor world. Originality/value: This study is the first to show that sentimental traders also factor rational information into the valuation process – an idea that was likely assumed prior to this study, but was never substantiated.